Severn School of Psychiatry education fellowships: a new way to promote educational practice and research. (April 2015) - Macpherson, Rob; Arulanandam, Sherlie; Undrill, Guy; Atkinson, Simon; Arnott, Steve; Hughes, Sian; Toogood, Hannah; Scheeres, Karl; Matone, Luciana
Summary: This paper describes a model of training in leadership and project management skills for advanced trainees, using educational projects within the Severn School of Psychiatry. Fellowships lasting 1 year have been developed to enable trainees, working with a senior consultant trainer associated with the School of Psychiatry, to support important new educational initiatives. Linkage with the local university training and learning for health professionals research module has provided academic support for the trainees and the projects. Four examples for the first year of the programme are described and feedback from structured interviews with participants is presented. The development of the fellowships appears to have had wider benefits, in developing educational faculty in the School of Psychiatry and the trainees involved have had opportunities to extend their project management and leadership skills. The fellowship programme is continuing to develop, based on feedback from its first successful year.